PERANCANGAN TAMPILAN VISUAL DOCKING GUIDANCE SYSTEM (VDGS) PADA SISTEM PARKIR PESAWAT TERBANG - Dermawan, Denny; Purnomo, Muhammad Jalu (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Visual Docking Guidance System (VDGS), is a device provided by the airport service to assist a pilot parked the plane on the righr place. On Aircraft parking control activities in the airport, the pilot is assisted by a marshaller that aims to be steering the movement of aircraft to the correct parking spot. The more density of the movement of aircraft on the apron activity requires the use of alternative technology to substitute marshaller, this technology is called Visual Docking Guidance Syatem (VDGS). VDGS display design uses three pieces o f board o f dot matrix display that is made into one to form a combination in accordance with the appearance on the VDGS on the market. Display used is a superbright LED dot matrix. The controller is a three pieces of. PIC 16F84A microcontroller and a series o f shift registers to display the movement of the aircraft to the right, to the left, straight and stops and also display the aircraft identity.